PERANAN POLA ASUH ORANG TUA TERHADAP KEIKUTSERTAAN SISWA DALAM KEGIATAN EKSTRAKURIKULER BOLAVOLI (STUDI PADA SMP NEGERI 1 KREJENGAN KRAKSAAN) - ANTANIA PUTRA, DIMAS (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Family is primary environment of every individual. As primary environment, the first and most intensive relationship between humans is happened in the family. Before a child knows wider environment, he or she knows his or her family environment and adsorbs norms, and values that applied in his or her family. That norms or values is used as part of his or her personality. So, we can see the differences between one and another. All of that, essentially it is formed by the norms and values that applied in family that derived by education and parenting to their child hereditarily. It is not surprising that the role of good parenting will support child’s activity,  otherwise bad parenting will slow down the child’s activity. The goal of this research is the role of parenting toward the joining of student and types of parenting that support the level of joining in volleyball extracurricular in Krejengan 1 State Junior High school, the population in this research is student of Krejengan 1 State Junior High school that joining volleyball extracurricular that consists of 33 persons. This research is non-experiment research, with Contingency-coefficient to do the data analysis. Based on this research this is influence of parenting role towards the student joining in volleyball extracurricular in Krejengan 1 State Junior High School, and the types of parenting that shows student with better joining level in vollyball extracurricular in Krejengan 1 State Junior High School is permissive parenting type that is 17 students (51.52%) and authoritative parenting type that is 16 students (48,48%) . Keywords : parents parenting, students joining